Behavior of concrete columns under various confinement effects - Abd El Fattah, Ahmed Mohsen (Kansas State University, 2012)
The analysis of concrete columns using unconfined concrete models is a well established practice. On the other hand, prediction of the actual ultimate capacity of confined concrete columns requires specialized nonlinear analysis. Modern codes and standards are introducing the need to perform extreme event analysis. There has been a number of studies that focused on the analysis and testing of concentric columns or cylinders. This case has the highest confinement utilization since the entire section is under confined compression. On the other hand, the augmentation of compressive strength and ductility due to full axial confinement is not applicable to pure bending and combined bending and axial load cases simply because the area of effective confined concrete in compression is reduced. The higher eccentricity causes smaller confined concrete region in compression yielding smaller increase in strength and ductility of concrete. Accordingly, the ultimate confined strength is gradually reduced from the fully confined value fcc (at zero eccentricity) to the unconfined value f’c (at infinite eccentricity) as a function of the compression area to total area ratio. The higher the eccentricity the smaller the confined concrete compression zone. This paradigm is used to implement adaptive eccentric model utilizing the well known Mander Model and Lam and Teng Model. Generalization of the moment of area approach is utilized based on proportional loading, finite layer procedure and the secant stiffness approach, in an iterative incremental numerical model to achieve equilibrium points of P- and M- response up to failure. This numerical analysis is adaptod to asses the confining effect in circular cross sectional columns confined with FRP and conventional lateral steel together; concrete filled steel tube (CFST) circular columns and rectangular columns confined with conventional lateral steel. This model is validated against experimental data found in literature. The comparison shows good correlation. Finally computer software is developed based on the non-linear numerical analysis. The software is equipped with an elegant graphics interface that assimilates input data, detail drawings, capacity diagrams and demand point mapping in a single sheet. Options for preliminary design, section and reinforcement selection are seamlessly integrated as well. The software generates 2D interaction diagrams for circular columns, 3D failure surface for rectangular columns and allows the user to determine the 2D interaction diagrams for any angle  between the x-axis and the resultant moment. Improvements to KDOT Bridge Design Manual using this software with reference to AASHTO LRFD are made. This study is limited to stub columns.
Keywords: Reinforced concrete columns; CFST; FRP wrapped columns; Columns subjected to biaxial bending; Civil Engineering (0543)